2009
DOI: 10.1128/iai.00198-09
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Genome of theEscherichia coliO157:H7 2006 Spinach-Associated Outbreak Isolate Indicates Candidate Genes That May Enhance Virulence

Abstract: In addition to causing diarrhea, Escherichia coli O157:H7 infection can lead to hemolytic-uremic syndrome (HUS), a severe disease characterized by hemolysis and renal failure. Differences in HUS frequency among E. coli O157:H7 outbreaks have been noted, but our understanding of bacterial factors that promote HUS is incomplete. In 2006, in an outbreak of E. coli O157:H7 caused by consumption of contaminated spinach, there was a notably high frequency of HUS. We sequenced the genome of the strain responsible (TW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
145
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(150 citation statements)
references
References 63 publications
3
145
1
1
Order By: Relevance
“…Stx2 has been associated with severe disease more frequently than Stx1 (Boerlin et al, 1999;Ethelberg et al, 2004), and was shown to be 400 times more potent than Stx1, in mice (Tesh et al, 1993). Mitomycin C treatment also led to increased induction of stx2 expression in TW14359 compared to Sakai (Kulasekara et al, 2009). Here we show that in the absence of DNA-damaging agents, baseline expression of stx2 is markedly higher in TW14359 relative to Sakai before and after epithelial cell exposure, suggesting that increased Stx2 production in this strain may play a role in HUS development.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Stx2 has been associated with severe disease more frequently than Stx1 (Boerlin et al, 1999;Ethelberg et al, 2004), and was shown to be 400 times more potent than Stx1, in mice (Tesh et al, 1993). Mitomycin C treatment also led to increased induction of stx2 expression in TW14359 compared to Sakai (Kulasekara et al, 2009). Here we show that in the absence of DNA-damaging agents, baseline expression of stx2 is markedly higher in TW14359 relative to Sakai before and after epithelial cell exposure, suggesting that increased Stx2 production in this strain may play a role in HUS development.…”
Section: Discussionmentioning
confidence: 98%
“…This could be due in part to an unrecognized gene or set of genes unique to TW14359. Indeed, the recent comparison of TW14359 and Sakai genomes identified several genes exclusive to TW14359, including putative TTSS effectors and an intact norV gene, the deletion of which is hypothesized to decrease colonization of the large intestine (Kulasekara et al, 2009). Future work should focus on comparing TTSS and effector protein levels between these strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genome analysis by octamer-based genomic scanning and microarraybased comparative genomic hybridization (Kim et al, 1999;Zhang et al, 2007) has shown that E. coli O157 : H7 can be assigned to three main phylogenetic lineages: termed lineages I, II and I/II. Typically, lineage I isolates originate from human clinical and bovine sources; whereas, lineage II strains predominantly have a bovine origin, while I/II strains are associated with human infection and include a hyper-virulent group consisting of the multistate 'spinach' outbreak strains Kulasekara et al, 2009;Laing et al, 2009). A key genetic signature of the three E. coli O157 : H7 lineages lies in the possession of different shiga toxin (stx) genes, carried by shiga toxin-encoding prophages.…”
Section: Introductionmentioning
confidence: 99%